Academic progress dependence from the studentsʼ group unity degree – New effective tool of enhancement - Цільмак, Олена Миколаївна; Цільмак, О. М.; Цильмак, Елена Николаевна; Tsilmak, Olena M.; Артьоменко, Володимир Вікторович; Артьоменко, В. В.; Артеменко, Владимир Викторович; Artomenko, Volodymyr V.; Artyomenko, Volodymyr (Inted2020 Proceedings : Valencia, 2020)
Teaching methods in modern society are constantly updated and improved. Since 2014, the new training exercise “The Human Body” (authored by O. M. Tsilmak and V. V. Artyomenko) was introduced into the educational process of the Odessa State University of Internal Affairs and the Odessa National Medical University. The main objectives of the tool were: 1. Systematization of students' knowledge about the basic functions of human organs and their significance for the functional activity of the human body. 2. Formation of students group unity. 3. Prevention of the occurrence of such a negative phenomenon in the study group as an outsider. The essence of the method: each student was offered cards with the names of human organs (kidney, heart, liver, spleen, stomach, etc.). It is noted that the main hypothesis of the method creation was: the degree of student group unity directly affects the success of the entire group of students training. First-year study groups were involved, 22 (637) - experimental and 22 (641) - control ones from Odessa State University of Internal Affairs and Odessa National Medical University took part in the research study. The indicators of academic performance were analyzed in all 44 study groups before the exercise and one year after. The results of the study showed that in 11 experimental groups of students of the University of Internal Affairs, the learning success increased by 23%, and among students of the Medical University by 18%. At the same time, in the control groups of students of the University of Internal Affairs, the success of studies decreased by 5%, and of the Medical University by 9%. Interviewing students about the reasons for improving academic performance, it was found that one of these reasons is group unity around the result of learning activities. Conclusion: The new learning tool — training exercise «The human body" confirmed the hypothesis put forward by authors and showed effectiveness and efficiency.

Методи навчання в сучасному суспільстві постійно оновлюються та вдосконалюються. З 2014 року до освітнього процесу Одеського державного університету внутрішніх справ та Одеського національного медичного університету було введено нову навчальну вправу «Людське тіло» (автори О. М. Цільмак та В. В. Артеменко). Основними завданнями інструменту були: 1. Систематизація знань учнів про основні функції людських органів та їх значення для функціональної діяльності людського організму. 2. Формування єдності учнівської групи. 3. Запобігання виникненню такого негативного явища в досліджуваній групі, як стороння особа. Суть методу: кожному студенту були запропоновані картки з назвами людських органів (нирки, серце, печінка, селезінка, шлунок тощо). Зазначається, що основною гіпотезою створення методу було: ступінь єдності студентської групи безпосередньо впливає на успішність підготовки всієї групи студентів. У дослідженні взяли участь групи першого курсу: 22 (637) - експериментальні та 22 (641) - контрольні групи Одеського державного університету внутрішніх справ та Одеського національного медичного університету. Показники академічної успішності аналізували у всіх 44 навчальних групах перед вправою та через рік після. Результати дослідження показали, що в 11 експериментальних групах студентів Університету внутрішніх справ успішність навчання зросла на 23%, а серед студентів Медуніверситету - на 18%. Водночас у контрольних групах студентів Університету внутрішніх справ успішність навчання знизилася на 5%, а Медуніверситету - на 9%. Опитуючи студентів щодо причин підвищення академічної успішності, було встановлено, що однією з цих причин є єдність групи навколо результату навчальної діяльності. Висновок: Новий навчальний інструмент - тренувальна вправа «Людське тіло» підтвердив висунуту авторами гіпотезу та продемонстрував ефективність та результативність.

Методы обучения в современном обществе постоянно обновляются и совершенствуются. С 2014 года в образовательный процесс Одесского государственного университета внутренних дел и Одесского национального медицинского университета было введено новое учебное упражнение «Человеческое тело» (авторы Е. Н. Цильмак и В. В. Артеменко). Основными задачами инструмента были: 1. Систематизация знаний учащихся об основных функциях человеческих органов и их значение для функциональной деятельности человеческого организма. 2. Формирование единства учебной группы. 3. Предотвращение возникновения такого негативного явления в исследуемой группе, как постороннее лицо. Суть метода: каждому студенту были предложены карточки с названиями человеческих органов (почки, сердце, печень, селезенка, желудок и т.д.). Отмечается, что основной гипотезой создания метода было: степень единства студенческой группы непосредственно влияет на успешность подготовки всей группы студентов. В исследовании приняли участие группы первого курса 22 (637) - экспериментальные и 22 (641) - контрольные группы Одесского государственного университета внутренних дел и Одесского национального медицинского университета. Показатели академической успеваемости анализировали во всех 44 учебных группах перед упражнением и через год после. Результаты исследования показали, что в 11 экспериментальных группах студентов Университета внутренних дел успешность обучения выросла на 23%, а среди студентов медуниверситета - на 18%. В то же время в контрольных группах студентов Университета внутренних дел успешность обучения снизилась на 5%, а медуниверситета - на 9%. При опросе студентов о причинах повышения академической успеваемости, было установлено, что одной из причин является единство группы вокруг результата учебной деятельности. Вывод: Новый учебный инструмент - тренировочная упражнение «Человеческое тело» подтвердил выдвинутую авторами гипотезу и продемонстрировал эффективность и результативность.
Tsilmak O. Academic progress dependence from the studentsʼ group unity degree – New effective tool of enhancement / O. Tsilmak, V. Artyomenko // 14th International Technology, Education and Development Conference (2-4 March, 2020) ; Inted2020 Proceedings. – Spain : Valencia, 2020. – Р. 2828-2833.
Keywords: students' academic progress; students’ motivation; undergraduate education; collaborative and active learning; non-technical skills; bullying prevention; академічний прогрес студентів; мотивація студентів; бакалаврська освіта; спільне та активне навчання; нетехнічні навички; запобігання булінгу; успеваемость студентов; мотивация студентов; бакалавриат; совместное и активное обучение; нетехнические навыки; предотвращение буллинга; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education